2016
DOI: 10.1096/fj.201500173
|View full text |Cite
|
Sign up to set email alerts
|

The matricellular protein CCN1 enhances TGF‐β1/SMAD3‐dependent profibrotic signaling in fibroblasts and contributes to fibrogenic responses to lung injury

Abstract: Matricellular proteins mediate pleiotropic effects during tissue injury and repair. CCN1 is a matricellular protein that has been implicated in angiogenesis, inflammation, and wound repair. In this study, we identified CCN1 as a gene that is differentially up-regulated in alveolar mesenchymal cells of human subjects with rapidly progressive idiopathic pulmonary fibrosis (IPF). Elevated levels of CCN1 mRNA were confirmed in lung tissues of IPF subjects undergoing lung transplantation, and CCN1 protein was predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 56 publications
2
48
0
Order By: Relevance
“…To understand the biological role of YAP1 in pancreatic cancer, we performed bioinformatic analyses of protein networks. The results revealed that YAP1 is directly connected to secreted AREG, CTGF, CYR61, FGF1 and MSLN that are involved in fibrosis and other key signaling pathways involved in the tumor-stroma interactions [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…To understand the biological role of YAP1 in pancreatic cancer, we performed bioinformatic analyses of protein networks. The results revealed that YAP1 is directly connected to secreted AREG, CTGF, CYR61, FGF1 and MSLN that are involved in fibrosis and other key signaling pathways involved in the tumor-stroma interactions [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all 7 genes that were classified as synergistic were YAP/TAZ targets (Fig 1F, S2 Table) and 9/13 of the genes classified as additive (Fig 1F, S2 Table) were also shown to be regulated by YAP/TAZ [13,[46][47][48][49][50]. Among these genes, CTGF [51,52], IL11 [53], EDN1 [54], SERPINE1/PAI-1 [55], F3/tissue factor [56], CYR61 [57], KLF10 [58], ATF3 [59], FZD8/Frizzled-8 [59] and RUNX1 [60] have been shown to be important profibrotic mediators. Gene expression profiles of these genes are shown in Fig 1G. These results suggested that LPA and TGFβ1 signalling converges on YAP/TAZ and that YAP/TAZ could represent a central node to regulate fibrotic responses.…”
Section: Whole Genome Expression Analysis Reveals Lpa-tgfβ1 Synergy Imentioning
confidence: 97%
“…Additionally, research has shown several genetic hotspots, such as the MUC5B promoter, associate with a worsened phenotype (3). Extra-cellular matrix proteins such as integrins and matricellular proteins have been associated with fibrosis (4, 5). Most saliently important is the cytokine Transforming Growth Factor β (TGF-β), which is well accepted as a driver of cellular fibrosis (5, 6).…”
mentioning
confidence: 99%